(untitled) (Research, Society and Development, 2021)
Inoculation with Azospirillum brasilense has potential for use in the cultivation of sorghum (Sorghum bicolor [L.] Moench) due to the possibility of altering the physiology and morphology of plants. In this sense, the present study aims to evaluate the influence of inoculation via seed with the growth promoting bacteria of the strain Azospirillum brasilense on the morphological composition, fermentative parameters, nutritional losses,strain on nitrogen and carbohydrate fractions in sorghum silage of the hybrid AG 2005. The experimental design was completely randomized, consisting in two treatments (with and without inoculation), with four replications of experimental silos. The nitrogen fractionation was determined as described by Licitra et al. (1996) and to measure the fractionation of carbohydrates, it was evaluated according to the methodology proposed by Lanzas et al. (2007). The inoculated plants showed a lower percentage of stalk, but there was a greater participation of panicles and more grains. The inoculated hybrid produced silage with a lower content of nitrogen insoluble in acid detergent (ADIN) and nitrogen insoluble in neutral detergent (NDIN). Regarding the fractionation of carbohydrates, the sorghum silages with inoculation differed significantly in CHO (total carbohydrates) and CC (indigestible fiber) in relation to the control. Regarding protein fractionation, the fraction (CP) being indigestible, the inoculation showed a reduction of 0.29 percentage units when compared to the control. Thus, the inoculation of seeds with A. brasilense may be a viable alternative, as it has the potential to reduce the insoluble and indigestible protein and glycid fraction in the gastrointestinal tract in sorghum silages.